The Moderating Effect of Resilience on Corporal Punishment Attitudes and Post-Traumatic Growth - Lanz Daenielle T Cordero; Patricia Isabel M Lafavilla; Bhea Rose A Angeles; Maria Alina Kryselle I Doong (Research Synergy Foundation Press, 2025)
Although many studies have investigated the relationship between experiences of Corporal Punishment (CP) and Post-Traumatic Growth (PTG), the connection between CP attitudes and PTG remains underexplored. Thus, this study aimed to determine the relationship between CP attitudes, specifically CP Myth Acceptance and PTG, while also investigating the moderating role of resilience among Filipino young adults. Using purposive sampling, data were collected in December 2024 from 153 respondents (ages 18-26) who experienced CP between the ages of 2 and 14 years, employing a descriptive-correlational design with moderation analysis. Results showed that respondents exhibited moderate levels of CP myth acceptance, indicating neutral beliefs about the harmlessness and necessity of CP. Similarly, moderate levels of PTG were observed, suggesting some degree of positive psychological growth following adverse experiences. Finally, the respondents’ resilience levels ranged from low to normal. Notably, the study found no significant relationship between CP Myth Acceptance and PTG (r = .085; p = .297), and resilience did not moderate this relationship (p = .983). These findings reveal the complexity of these constructs—suggesting that cognitive frameworks, such as CP attitudes, are not good predictors of PTG while emphasizing the distinction between resilience as a protective factor and PTG as a growth-facilitating factor. An action plan was proposed, including educational webinars to challenge CP myths and workshops to promote PTG and resilience-building programs. This research contributes to a deeper understanding of the connections between the target constructs, offering insights into interventions for enhancing emotional well-being and trauma recovery among Filipino young adult victims of corporal punishment.